Disinvestment from low value clinical interventions: NICEly done?. (27th July 2011) - Garner, Sarah; Littlejohns, Peter
Abstract : Over the past 10 years NICE has identified over 800 clinical interventions for potential disinvestment. But Sarah Garner and Peter Littlejohns report that although disinvestment will increase efficiency and quality, the opportunity for cash saving is unlikely to meet the necessary targets